Gibberellin derivative GA-13315 overcomes multidrug resistance in breast cancer by up-regulating BMP6 expression - Luo, Xianqiang; Wang, Guohui; Wang, Yuting; Wang, Meichen; Tan, Zhuomin; Luo, Min; Zhang, Limei; Song, Yan; Jia, Yinnong; Zhou, Hongyu; Qing, Chen (Frontiers in Pharmacology, 2022)
Chemoresistance represents a major obstacle in breast cancer treatment. Bone morphogenetic protein 6 (BMP6) was reported to participate in the occurrence and development of various tumors. In the present study, the results of transcriptome sequencing, qRT-PCR and western blot analysis revealed that BMP6 was down-regulated in multidrug resistant MCF-7/Adr breast cancer cells and BMP6 overexpression sensitized MCF-7/Adr cells to chemotherapeutic drugs, indicating that BMP6 downregulation was involved in the mechanisms of multidrug resistance (MDR) of MCF-7/Adr breast cancer cells. GA-13315 (GA5) is a new tetracyclic diterpenoid selected from a series of gibberellin derivatives. Here, we found that GA5 exhibited more potent anti-tumor activity in multidrug resistant MCF-7/Adr breast cancer cells and xenografts, indicating that GA5 could overcome MDR. Mechanistically, GA5 increased BMP6 expression, and BPM6 knockdown partially reversed the inhibitory effect of GA5 on cell proliferation. Furthermore, we found that ERK phosphorylation and P-gp expression were increased in MCF-7/Adr cells when compared with MCF-7 cells. Either overexpression of BMP6 or treatment the cells with GA5 significantly decreased ERK phosphorylation and P-gp expression, indicating that GA5 reversed MDR of MCF-7/Adr cells by upregulating BMP6, thereby inhibiting the activation of ERK signaling pathway and reducing P-gp expression. Collectively, our present study demonstrated that the MDR of MCF-7/Adr cells was closely related to the low expression of BMP6, and revealed the molecular mechanisms by which GA5 overcame MDR in breast cancer, providing evidence in supporting the development of GA5 to be a promising agent for overcoming MDR in clinical cancer therapy in the future.